Recovery of the Cholangiocytes After Ischemia and Reperfusion Injury: Ultra-Structural, Hystological and Molecular Assessment in Rats - Aloia, Thiago P.A. (J Clin Exp Hepatol, 2018)
INTRODUCTION: Ischemia–reperfusion (I/R) injury of the liver is a common area of interest to transplant and hepatic surgery. Nevertheless, most of the current knowledge of I/R of the liver derives from the hepatocyte and little is known of what happens to the cholangiocytes. Herein, we assess the sequence of early events involved in the I/R injury of the cholangiocytes. METHODS: Sixty Wistar rats were randomized in a SHAM group and I/R group. Serum biochemistry, histopathology, immunohistochemistry, transmission electron microscopy (TEM) and laser capture microdissection (LCM) were used for group comparison. RESULTS: There was peak of alkaline phosphatase 24 h after IR injury, and an increase of aspartate aminotransferase and alanine aminotransferase after 6 h of reperfusion, followed by a return to normal levels 24 h after injury. The I/R group presented the liver parenchyma with hepatocellular degeneration up to 6 h, followed by hepatocellular necrosis at 24 h. TEM showed cholangiocyte injury, including a progressive nuclear degeneration and cell membrane rupture, beginning at 6 h and peaking at 24 h after reperfusion. Cytokeratin-18 and caspase-3-positive areas were observed in the I/R group, peaking at 24-h reperfusion. Anti-apoptotic genes Bcl-2 and Bcl-xl activity were expressed from 6 through 24 h after reperfusion. BAX expression showed an increase for 24 h. CONCLUSIONS: I/R injury to the cholangiocyte occurs from 6 through 24 h after reperfusion and a combination of TEM, immunohistochemistry and LCM allows a better isolation of the cholangiocyte and a proper investigation of the events related to the I/R injury. Apoptosis is certainly involved in the I/R process, particularly mediated by BAX.